Analisis Strategi Meningkatkan Keterampilan Menulis Permulaan Peserta Didik di Sekolah Dasar: Kajian Literatur - Louisa Ananta; Elfia Sukma; Ingria Kharisma (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Writing skills are one of the foundations in the educational journey towards a higher level. It is important to find the right strategy to improve writing skills, especially in beginning writing in students. Therefore, this study is expected to help educators know the right strategy to improve beginning writing skills in students. The method used in this study is a Literature Study (library research); with a review of journals and articles from previous studies related to this research. It is recommended that teachers and curriculum developers and create updated strategies to improve beginning writing skills for students in elementary schools.